2009
DOI: 10.1287/msom.1080.0221
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing and Inventory Control of Substitute Products

Abstract: We study dynamic pricing and inventory control of substitute products for a retailer who faces a long supply lead time and a short selling season. Within a multinomial logit model of consumer choice over substitutes, we develop a stochastic dynamic programming formulation and derive the optimal dynamic pricing policy. We prove that dynamic pricing converges to static pricing as inventory levels of all variates approach the number of remaining selling periods (assuming at most one customer arrival within each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
172
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(177 citation statements)
references
References 29 publications
4
172
0
1
Order By: Relevance
“…The objective is to maximize the expected revenue per customer. For the pricing problem, Hanson and Martin (1996) notice that the expected revenue function fails to be concave in prices for the multinomial logit model, but significant progress was made by formulating the pricing problem in terms of market shares, as this results in a concave expected revenue function; see Song and Xue (2007) and Dong et al (2009). Li and Huh (2011) extend the concavity result to the nested logit model by assuming that the price sensitivities of the products are constant within each nest and the nest dissimilarity parameters are all between zero and one.…”
mentioning
confidence: 99%
“…The objective is to maximize the expected revenue per customer. For the pricing problem, Hanson and Martin (1996) notice that the expected revenue function fails to be concave in prices for the multinomial logit model, but significant progress was made by formulating the pricing problem in terms of market shares, as this results in a concave expected revenue function; see Song and Xue (2007) and Dong et al (2009). Li and Huh (2011) extend the concavity result to the nested logit model by assuming that the price sensitivities of the products are constant within each nest and the nest dissimilarity parameters are all between zero and one.…”
mentioning
confidence: 99%
“…Inventory-driven substitution research has been studied by many Kuyumcu and Popescu [14] studied joint pricing and inventory control by considering deterministic optimization models for multiple substitutable products, and they showed that the optimization problem could be reduced to a pure pricing problem. Karakul and Chan [3] considered stochastic optimization problems, which are a joint pricing and inventory decision, for an existing product and a new improved production decisions. The authors developed an in-depth mathematical procedure for finding optimal solutions for the stochastic problem with inventory-driven substitution.…”
Section: Most Research Papers In Operations Researchmentioning
confidence: 99%
“…1~8 (in 100,000s). 3 The expected profit of the capacity level decision model when     ,     ,     . 4 The expected profit of joint pricing and capacity level decision without inventory-driven substitution 5 The expected profit of the pricing decision model when 3 The expected profit of the capacity level decision model when         ,     .…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to Anderson et al (1992) for a comprehensive coverage of MNL models in general and to Wierenga (2008) for their use in marketing science. MNL and its variations (e.g., nested logit) have been extensively used to model consumer behavior in the operations management literature as well, in particular in the context of pricing, revenue management and assortment planning (Hanson and Martin 1996, van Ryzin and Mahajan 1999, Dong et al 2009, Zhang and Adelman 2009, Davis et al 2014. In this stream, the need for richer and more general choice models has also been recognized and some propositions have been made, such as Talluri and van Ryzin (2004), Alptekinoğlu and Semple (2015), Blanchet et al (2016), Srikanth and Rusmevichientong (2016).…”
mentioning
confidence: 99%